The impact of lockdown in Wuhan on residents confidence in controlling COVID-19 outbreak at the destination cities - Guo, Xiaoxin; Zhong, Shihu; Wu, Yidong; Zhang, Yalin; Wang, Zhen (Frontiers in Public Health, 2022)
Objective: From January 23rd, 2020, lock-down measures were adopted in Wuhan, China to stop the spread of COVID-19. However, due to the approach of the Spring Festival and the nature of COVID-19, more than 6 million permanent and temporary residents of Wuhan (who were potential carriers or spreaders of the virus), left the city before the lock-down measures were implemented. This study aims to explore whether and how the population inflow from Wuhan city impacted residents’ confidence in controlling COVID-19 outbreak at the destination cities. Study Design and Setting: Based on questionnaire data and migration big data, a multiple regression model was developed to quantify the impact of the population inflow from Wuhan city on the sense of confidence of residents in controlling COVID-19 outbreak at the destination cities. Scenarios were considered that varied residents’ expected month for controlling COVID-19 outbreak at the destination cities, residents’ confidence in controlling COVID-19 outbreak at the destination cities, and the overall indicators for the sense of confidence of residents in controlling COVID-19. A marginal effect analysis was also conducted to calculate the probability of change in residents’ confidence in controlling COVID-19 outbreak with per unit change in the population inflow from Wuhan city. Results: The impact of population inflow from Wuhan city on residents’ expected month for controlling COVID-19 outbreak at the destination cities was positive and significant at the 1% level, while that on residents’ confidence in controlling COVID-19 at the destination cities was negative and significant at the 1% level. Robustness checks, which included modifying the sample range and replacing measurement indicators of the population inflow from Wuhan city, demonstrated these findings were robust and credible. Conclusion: The population inflow from Wuhan city played a negative role in the sense of confidence of residents in controlling COVID-19 at the destination cities. The higher the population inflow from Wuhan city, the longer the residents’ expected month for controlling COVID-19 outbreak at the destination cities became, and the weaker the residents’ confidence in controlling COVID-19 outbreak at the destination cities.